2021
DOI: 10.5194/acp-21-10229-2021
|View full text |Cite
|
Sign up to set email alerts
|

Role of oceanic ozone deposition in explaining temporal variability in surface ozone at High Arctic sites

Abstract: Abstract. Dry deposition is an important removal mechanism for tropospheric ozone (O3). Currently, O3 deposition to oceans in atmospheric chemistry and transport models (ACTMs) is generally represented using constant surface uptake resistances. This occurs despite the role of solubility, waterside turbulence and O3 reacting with ocean water reactants such as iodide resulting in substantial spatiotemporal variability in O3 deposition and concentrations in marine boundary layers. We hypothesize that O3 depositio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 83 publications
1
8
0
Order By: Relevance
“…Based on this generalized ozone climatology, we assessed the quality of available global (MACC and CAMSRA) and regional (CAM-SRAQ) reanalysis products for northern Fennoscandia focusing on the seasonality of ozone. We confirm previously published results concerning the quality of global reanalysis products (Huijnen et al, 2020;Barten et al, 2021) and find that the observed ozone patterns in northern Fennoscandia are not reproduced well. Better performance was displayed by the regional model reanalysis CAMSRAQ ensemble which reproduces the observed ozone seasonality well, although with a remaining annual average deviation of up to −7 ppb.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Based on this generalized ozone climatology, we assessed the quality of available global (MACC and CAMSRA) and regional (CAM-SRAQ) reanalysis products for northern Fennoscandia focusing on the seasonality of ozone. We confirm previously published results concerning the quality of global reanalysis products (Huijnen et al, 2020;Barten et al, 2021) and find that the observed ozone patterns in northern Fennoscandia are not reproduced well. Better performance was displayed by the regional model reanalysis CAMSRAQ ensemble which reproduces the observed ozone seasonality well, although with a remaining annual average deviation of up to −7 ppb.…”
Section: Discussionsupporting
confidence: 71%
“…In terms of atmospheric chemistry, this includes meteorological data as well as observations of chemical substances from, for example, satellite, airborne instruments, and ground-level monitoring station networks. Global reanalyses, however, have already been shown to underestimate [O 3 ] particularly over the polar region (Huijnen et al, 2020;Barten et al, 2021). Barten et al (2021) suggest that global reanalysis products that only assimilate satellite products do not sufficiently cover [O 3 ] variations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, other model deficiencies could also play a role, including dry deposition and NO x lifetime. Indeed, Barten et al (2021) found that overestimation of oceanic O 3 deposition can explain some differences between modeled and measured surface O 3 in the high Arctic. Some models in Fig.…”
Section: Surface O 3 Model Evaluationmentioning
confidence: 99%
“…Using the improved (or new) parameterisation, Luhar et al (2018) estimated an oceanic dry deposition of 98.4 ± 30.0 Tg O 3 yr −1 and a global one of 722.8 ± 87.3 Tg O 3 yr −1 (averaged over the years 2003-2012), which can be compared with the respective values 340 and 978 ± 127 Tg O 3 yr −1 obtained by Hardacre et al (2015) based on 15 global chemistry transport models (for the year 2001) using Wesely's scheme, demonstrating the large reduction in the oceanic value using the new parameterisation. The new approach was recently evaluated by other researchers in both global and regional models with various changes to the input parameter values (Loades et al, 2020;Barten et al, 2021).…”
Section: Ozone Dry Deposition Scheme For the Oceanmentioning
confidence: 99%